TRADISI TASAWUF DI PONDOK PESANTREN TEBUIRENG: EKSISTENSI, KARAKTERISTIK, DAN PERANNYA - Moh. Chalilurrosyid; Ach. Maimun; Moh Diyaul Murtadho; Abdullah; Fadlillah; Suji; Moh. Kurdi (Jurnal Ikhtibar Nusantara, 2026)
This study aims to analyze the influence of student organizations on students’ intellectual, emotional, and spiritual intelligence at Harisul Khairaat Ome Islamic Boarding School, Tidore Islands City. Student organizations serve as a forum for student development, particularly in fostering leadership skills, responsibility, discipline, cooperation, and character formation. Therefore, their presence is expected to contribute to the enhancement of students’ intellectual, emotional, and spiritual intelligence. This study employed a quantitative approach with a causal-associative research design. The research population consisted of 53 students, all of whom were selected as the sample using a total sampling technique. Data were collected through a questionnaire using a Likert scale. Prior to its use, the research instrument was tested for validity using Pearson’s Product-Moment correlation and for reliability using Cronbach’s Alpha. The data were analyzed using descriptive statistics, classical assumption tests consisting of normality and heteroscedasticity tests, and simple linear regression analysis. Hypothesis testing was conducted using a partial t-test and the coefficient of determination (R²) with the assistance of IBM SPSS Statistics version 31. The findings indicate that student organizations have a positive and significant influence on students’ intellectual, emotional, and spiritual intelligence. The regression analysis produced the equation Y = 28.181 + 0.420X, indicating that every one-unit increase in student organization involvement increases the intellectual, emotional, and spiritual intelligence score by 0.420. The t-test yielded a calculated t-value of 3.268 with a significance value of 0.002, which is lower than 0.05. Therefore, the research hypothesis was accepted. It can be concluded that student organizations have a significant influence on students’ intellectual, emotional, and spiritual intelligence at Harisul Khairaat Ome Islamic Boarding School, Tidore Islands City. Keywords: student organization, intellectual intelligence, emotional intelligence, spiritual intelligence, Islamic boarding school